Quality of life of people living with sex development disorders and sex re-assignment in Nigeria - Muhammad Sani, Abdurrahman (2018)
Disorders of sex development is a complex medical, social and psychological emergency that required prompt intervention in the treatment of the condition. Sex assignment is considered as an emergency issue and as such should not be delayed, this is due to social and psychological crisis that parents and patients may undergoes as a result of ambiguous genitalia. The quality of life of people with disorders of sex development depends largely on the psychosocial management of the condition. Early diagnosis and proper counselling facilitate appropriate management and produce positive outcome. In Nigeria, many people living with disorders of sex development faced serious psychological and social traumas such as marginalization, rejection, isolation, feeling of sadness, feeling of uncertainty, and feeling of shame. Although, disorders of sex development has received a considerable level of interest from medical practitioners, researchers and human right groups in the last decade; little is focused on the quality of life of people living with disorders of sex development. In Nigeria, there are few studies conducted in the field of disorders of sex development and most of the studies employed quantitative paradigms. Therefore the need to explore and described the quality of life of people living with disorders of sex development in Nigeria using qualitative paradigm. The study was guided by quality of life model to understand the quality of life of people living with disorders of sex development and sex re-assignment in Nigeria. The overarching research question of the study is; what are the quality of life of people with disorders of sex development and sex re-assignment in Nigeria? The specifi research questions are: what are the physical, psychological, social and spiritual experiences of as well as the treatment process employed by people living with disorders of sex development and sex re-assignment in Nigeria. This study employed qualitative approach using phenomenological research design. Non probability purposive sampling technique was used to recruit 13 people living with disorders of sex development and sex re-assignment in Nigeria. The participants had been diagnosed and treated with disorders of sex development and sex re-assignment in Nigeria for at least 6 months. The data were collected primarily through face to face interviews. The data were analysed using the principles of interpretative phenomenological analysis with the aid of NVivo software. Field notes from observation and documents analysis were used to triangulate the data. Data analysis revealed 15 major themes which answer the overarching research question; what are the quality of life of people with disorders of sex development and sex re-assignment in Nigeria. The major themes are: physical wellbeing and symptoms, infertility, psychological impact of DSD, lower self esteem, feeling about body ambiguity, socialization and social relationship, spiritual wellbeing, spiritual adaptation to DSD and life management. Others are identification of the condition, sex re-assignment, patients’ treatment concerns, and nursing experience. The findings indicated that disorder of sex development affect the quality of life of the people physically, psychologically, socially and spiritually. The findings of this study were in line with the Ferrel’s quality of life model. The findings provided information on the quality of life of people with disorders of sex development and sex re-assignment in Nigeria. The study contributed in the field of quality of life of people with disorders of sex development by adding treatment process and nursing experiences to the model. It would help the healthcare professionals in the provision of quality care with the view of improving the quality of life of people with disorders of sex development and sex re-assignment. There is need for research study on the impact of nursing care on the quality of life of people with DSD.